Untermeyer-Frost collection - Untermeyer, Louis, 1885-1977.; Frost, Robert, 1874-1963.; Frost, Robert, 1874-1963.
Letters from Robert Frost to Untermeyer dealing with poets and poetry, religion, politics, Frost's philosophy, and other interests of the two men; poetry, articles, pamphlets, and books of Frost's work and autographed photographs; together with drafts and galley proofs of The Letters of Robert Frost to Louis Untermeyer (1963) and correspondence, clippings, and other printed matter concerning Frost collected by Untermeyer.
Poet, critic, and editor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Frost, Robert, -- 1874-1963 -- Correspondence; Frost, Robert, -- 1874-1963 -- Philosophy; Untermeyer, Louis, -- 1885-1977 -- Correspondence; Philosophy; Poetry; Poets, American -- 20th century -- Correspondence; Religion; United States -- Politics and government; Critics; Editors; Poets